2017
DOI: 10.1159/000455241
|View full text |Cite
|
Sign up to set email alerts
|

Early Cholecystectomy for Acute Cholecystitis in the Elderly Population: A Systematic Review and Meta-Analysis

Abstract: Background: In the era of advanced surgical techniques and improved perioperative care, the willingness to perform emergency operations in elderly patients continues to increase. This systematic review aimed at assessing the clinical outcomes of early cholecystectomy in elderly patients with acute cholecystitis. Methods: Medline, Embase, and Cochrane Library databases were systematically searched for studies reporting on early cholecystectomy for acute cholecystitis in patients aged ≥70 years. The conversion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 39 publications
0
63
1
4
Order By: Relevance
“…7 A recent meta-analysis in 2017 has reported a perioperative morbidity of 24% and a mortality of 3.5% in AC patients aged ≥70 years undergoing early cholecystectomy, suggesting that early cholecystectomy is a feasible treatment, even in elderly AC patients. 9 Of note, the proportion of AC patients aged ≥80 years who received percutaneous drainage as a definitive first-line treatment without subsequent cholecystectomy significantly increased over time in the current study. A report from Taiwan also showed that the rate of percutaneous cholecystostomy (PC) in the AC patients ≥70 years of age increased from 7.2% in 2010 to 31.8% in 2015.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…7 A recent meta-analysis in 2017 has reported a perioperative morbidity of 24% and a mortality of 3.5% in AC patients aged ≥70 years undergoing early cholecystectomy, suggesting that early cholecystectomy is a feasible treatment, even in elderly AC patients. 9 Of note, the proportion of AC patients aged ≥80 years who received percutaneous drainage as a definitive first-line treatment without subsequent cholecystectomy significantly increased over time in the current study. A report from Taiwan also showed that the rate of percutaneous cholecystostomy (PC) in the AC patients ≥70 years of age increased from 7.2% in 2010 to 31.8% in 2015.…”
Section: Discussionmentioning
confidence: 55%
“…Conversely, however, Fuks et al found no significant differences in the rate of postoperative complications between elderly grade I or II AC patients aged ≥75 years and their younger counterparts, although the elderly participants had a higher Charlson Comorbidity Index than the younger patients . A recent meta‐analysis in 2017 has reported a perioperative morbidity of 24% and a mortality of 3.5% in AC patients aged ≥70 years undergoing early cholecystectomy, suggesting that early cholecystectomy is a feasible treatment, even in elderly AC patients …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, DLC has been defined, for example, as surgery performed 6-12 weeks after symptom onset or 7-45 days after admission (3)(4)(5). In addition, reports vary as to whether percutaneous transhepatic gallbladder drainage (PTGBD) performed before DLC is beneficial (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%